A semi-quantitative risk model for dairy farms to pinpoint and break source-pathway connections between nutrient sources and open drainage channel sections - Opoku, D. G.; Healy, M. G.; Fenton, O.; Daly, K.; Condon, T.; Tuohy, P. (Frontiers in Environmental Science, 2024)
Introduction On intensive grassland dairy farms in high rainfall areas with poorly drained soils, networks of open drainage channels linked to in-field drainage systems are needed to enable farm operations. Nitrogen and phosphorus point and diffuse sources may be connected to this open drainage channel network along surface and subsurface pathways, with negative impacts upon delivery to the downstream aquatic system. Methods This study developed a semi-quantitative risk assessment model by: (1) selecting parameters (categorical or continuous) representing the nutrient transfer continuum and (2) scoring (relative magnitude and impact) the risk of nutrient source connectivity and delivery for every open drainage channel section across seven dairy farms. Results and Discussion A Risk Index Classification System consisting of low, medium, high, or very high-risk class was developed, with high or above requiring a mitigation plan. Results showed that 23%, 68%, 9% and 0% of all open drainage channels on study farms were identified as low, moderate, high and very high-risk, respectively. A range from 2% to 25% per farm of the open drainage channels was classified as high-risk that potentially needed mitigation, although none was identified as very high-risk. Two-thirds of the high-risk open drainage channels were connected to the farmyards, with potential for high nutrient loss from point sources. A combined approach of source management and targeted breaking of the pathway (e.g., in-channel filters, water diversion bars) may help minimise nutrient losses from high risk open drainage channels on poorly draining soils.